Sistemska družinska psihologija - skozi psihoterapevtsko prakso - Eigen, Carole (Psihološka obzorja (Ljubljana), 1995)
Carole Eigen, Ph. D., a licenced American psychologist and family therapist, presented this paper as a part of the programme of studies in clinical psychology at the Department of Psychology at the University of Ljubljana. She kindly allowed to publish this article in this journal. Theoretical and clinical background is presented through the psychotherapeutic process of a marital couple from her private practice. It islearly demonstrated how healthy and problem making attitudes in a family system fit together and how a problem making systrm of communication and relationship holds itself unless professional help is been found.
Keywords: družina; family; sistemska teorija; psychology; psihologija; družinski odnosi; klinična psihologija; psihoterapija